Chapter Dall'archeologia globale dei paesaggi alla storia del territorio: un progetto di saperi essenziali per la definizione di valori, invarianti, statuti dell'eco-territorialismo - VOLPE, GIULIANO (Territori, 2023)
In recent decades, archaeology has undergone a process of deep transformation and epistemological refounding. A global and contextual vision has been succeding in the reading of stratified landscapes through a multidisciplinary study of artefacts and ecofacts, in order to reconstruct the relationships between society and the environment. Thus understood, archaeology also aims at contributing to the construction of 'place consciousness' and the emergence of 'heritage communities' by fostering participation and forms of social protection of territorial heritages.